2019
DOI: 10.1002/nafm.10270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Riparian Timber Harvest on Southeast Alaska Stream Habitat after 30–40 Years: Insights for Management

Abstract: Logging regulations in the Pacific Northwest and Alaska have evolved over time to alleviate the negative effects that historic harvest practices have had on stream habitat. While natural landscape factors largely control stream habitat, timber harvest can alter these influences, underscoring the importance of clarifying the effects of both for understanding and managing habitat in streams. We sampled areas in Southeast Alaska that had riparian zones harvested between 1980 and 1990, a period of less-restrictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 71 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Hunt and Royall (2013) noted that the examination of historical maps revealed that there were four mill ponds on North Buffalo Creek, which acted as sediment reservoirs during the expansion of Greensboro. While we do not have any absolute ages of LW at our study sites, it is possible that legacy wood—wood that was buried during the aggradation phase and subsequently exposed during the erosional phase—might comprise a significant portion of the highly decayed wood load, as has been found in other environments (Ross, Infante, Martin, & Rey, 2019). We also speculate that legacy wood could make up a significant portion of the wood budget in many urban streams, especially in the Piedmont region of the United States.…”
Section: Discussionmentioning
confidence: 94%
“…Hunt and Royall (2013) noted that the examination of historical maps revealed that there were four mill ponds on North Buffalo Creek, which acted as sediment reservoirs during the expansion of Greensboro. While we do not have any absolute ages of LW at our study sites, it is possible that legacy wood—wood that was buried during the aggradation phase and subsequently exposed during the erosional phase—might comprise a significant portion of the highly decayed wood load, as has been found in other environments (Ross, Infante, Martin, & Rey, 2019). We also speculate that legacy wood could make up a significant portion of the wood budget in many urban streams, especially in the Piedmont region of the United States.…”
Section: Discussionmentioning
confidence: 94%
“…Additional time between evaluations may also have allowed characteristics such as pool depths to adjust to the presence of additional wood in the channel (Ross et al. 2019). A change in wood frequency and pool depth did occur in the same stream reach in 9 (12%) of the 75 reaches where two or three attributes changed substantially, but this combination was not significantly more likely than expected.…”
Section: Discussionmentioning
confidence: 99%